CEO compensation and bank mergers - Bliss, R (Journal of Financial Economics, 2001)
Recent bank mergers generally did not improve relative operating performance or produce positive abnormal returns to acquiring bank shareholders. We examine the relationship between mergers and CEO compensation during 1986–1995, a period marked by overcapacity and frequent mergers. We find that mergers have a net positive effect on compensation, mainly via the effect of size on compensation. Compensation generally increases even if mergers cause the acquiring bank's stock price to decline, as is typical after a merger announcement. The form of compensation affects merger decisions, since CEOs with more stock-based compensation were less likely to make an acquisition.